HETEROCYCLIC SYNTHESIS USING NITRILIMINES: PART 18. SYNTHESIS OF NEW FUSED HETEROCYCLES CONTAINING TRIAZINONE MOIETY - Dalloul, Hany Mahmod (Makara Journal of Science, 2011)
A series of new 4,5-dihydro-6-oxo-1,2,4-triazino[4,5-b]1,2,3,4-tetrahydro-β-carbolines were synthesized by the reaction of methyl 1,2,3,4-tetrahydro-β-carboline-3-carboxylate and the appropriate hydrazonoyl halide in presence of triethylamine. The structures of the title compounds have been established by their elemental analyses and spectroscopecal data. The microbial features of some of the synthesized compounds were studied by a known method